2005
DOI: 10.1016/j.molcel.2005.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Smurf2 Ubiquitin Ligase Activity by Anchoring the E2 to the HECT Domain

Abstract: The conjugation of ubiquitin to proteins involves a cascade of activating (E1), conjugating (E2), and ubiquitin-ligating (E3) type enzymes that commonly signal protein destruction. In TGFbeta signaling the inhibitory protein Smad7 recruits Smurf2, an E3 of the C2-WW-HECT domain class, to the TGFbeta receptor complex to facilitate receptor degradation. Here, we demonstrate that the amino-terminal domain (NTD) of Smad7 stimulates Smurf activity by recruiting the E2, UbcH7, to the HECT domain. A 2.1 A resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
219
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(229 citation statements)
references
References 20 publications
8
219
1
1
Order By: Relevance
“…The domain of Nedd4-2 responsible for substrate binding and how it is affected by phosphorylation has not been identified. Smurf2, a HECT E3 ligase involved in TGF-␤ signaling, was shown to be regulated by a mechanism involving an interaction with phosphorylated Smad7, which in turn facilitates the recruitment of Ubc7 (24). In addition, the activity of the recently described HECT E3 ligase Mule͞ARF-BP1 is negatively regulated by its binding partner ARF (25), and we speculate that phosphorylation may modulate the substrate specificity of this enzyme, thereby explaining its diametrically opposed, substrate-dependent effects on cell survival (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The domain of Nedd4-2 responsible for substrate binding and how it is affected by phosphorylation has not been identified. Smurf2, a HECT E3 ligase involved in TGF-␤ signaling, was shown to be regulated by a mechanism involving an interaction with phosphorylated Smad7, which in turn facilitates the recruitment of Ubc7 (24). In addition, the activity of the recently described HECT E3 ligase Mule͞ARF-BP1 is negatively regulated by its binding partner ARF (25), and we speculate that phosphorylation may modulate the substrate specificity of this enzyme, thereby explaining its diametrically opposed, substrate-dependent effects on cell survival (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The HECT C-lobe is very flexible in position, and its function requires oscillation between different orientations (32). One places the active site cysteine close to the E2 site, where it can receive ubiquitin (as exemplified by the crystal structure of WWP1) (33), and another places it far away, in a conformation that allows transfer of ubiquitin to a substrate lysine (as seen in the Smurf2 crystal structure) (21). The changes induced by heclin are unlikely to reflect direct contact with this small ligand but are, instead, consistent with movement of the C-lobe from a conformation similar to that in the WWP1 crystal to one more similar to that in the Smurf2 crystal (Fig.…”
Section: Significancementioning
confidence: 99%
“…The C2 domain of Smurfs also tethers the I-Smad/Smurf complex to lipid rafts at cell membranes where binding and ubiquitination of receptors are executed [28]. In this complex, the N-terminal part of Smad7 facilitates Smurf2 activity by helping recruit the E2 conjugating enzyme UbcH7 [29]. Recently, it was shown that the heat shock protein 90 (Hsp90) is a modifier of Smurf2-mediated receptor ubiquitination, as inhibiting Hsp90 activity led to an increased receptor ubiquitination [30].…”
Section: Regulation Of Tgfβ Receptor Stabilitymentioning
confidence: 99%